The Role of Tonsillectomy in Adults with Tonsillar Hypertrophy and Obstructive Sleep Apnea. (28th March 2017) - Smith, Matthew M.; Peterson, Ed; Yaremchuk, Kathleen L.
Abstract : Objective: To determine if tonsillectomy alone is an effective treatment in improving obstructive sleep apnea in adult subjects with tonsillar hypertrophy and to evaluate the effect of tonsillectomy on patient‐reported quality‐of‐life indices. Study Design: Case series with planned data collection. Setting: Academic hospital. Subjects and Methods: Thirty‐four subjects completed enrollment and intervention from January 2011 to January 2016. Subjects completed pre‐ and postoperative quality‐of‐life questionnaires, including the Insomnia Severity Index, Epworth Sleepiness Scale, and the Functional Outcomes of Sleep Questionnaire–10. Surgical response to treatment was defined by a >50% decrease in the Apnea‐Hypopnea Index and a decrease in the overall Apnea‐Hypopnea Index to <20. Wilcoxon matched‐pairs signed‐rank tests were used to test each variable to assess for a change from pre‐ to postintervention. Subjects were then split into 3 BMI subgroups, with results also evaluated by Wilcoxon matched‐pairs signed‐rank tests. Results: There was a significant difference discovered between the mean preoperative Apnea‐Hypopnea Index of 31.57 and the mean postoperative value of 8.12 ( P <. 001). All patient‐reported outcomes improved significantly following tonsillectomy. After stratifying all outcome variables (Apnea‐Hypopnea Index, Epworth Sleepiness Scale, Insomnia Severity Index, and Functional Outcomes of Sleep Questionnaire–10) by sex, race, and tonsil size, no statistically significant difference was noted among any of these subgroups. There was a 78% surgical response to treatment. Conclusion: Tonsillectomy appears to be an effective treatment for obstructive sleep apnea in a select population of adults with tonsillar hypertrophy.